2018
DOI: 10.3390/jcs2010011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Processing Parameters for Thermoplastic Biocomposites Based on Hybrid Yarns Using Finite Elements Simulation

Abstract: This paper investigates the processing parameters for the compression molding of hemp/PLA hybrid yarn biocomposites and their effect on the final mechanical properties. Finite element simulations are used to develop and assess the processing parameters, pressure, temperature, and time. These parameters are then evaluated experimentally by producing the composites by two different methods, to compare the results of experimentally determined processing conditions to parameters determined by the simulation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…El-Shekeil et al 17 studied the effect of different processing parameters such as temperature, time and speed on the tensile properties of thermoplastic polyurethane (TPU) reinforced short kenaf fibre composites and found that optimum values of 190°C, 11 min, and 40 r/min, of temperature, time and speed, respectively, gave the best tensile properties. Vogt et al 16 also obtained vast improved results with considerably reduction in processing times to only 3 min as a function of temperature. When processing engineering thermoplastic polymers, it is necessary that the processing temperature is high enough to be able to melt the thermoplastic material and to enable a relatively quick heat transfer throughout the whole structure for homogeneous mixing.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…El-Shekeil et al 17 studied the effect of different processing parameters such as temperature, time and speed on the tensile properties of thermoplastic polyurethane (TPU) reinforced short kenaf fibre composites and found that optimum values of 190°C, 11 min, and 40 r/min, of temperature, time and speed, respectively, gave the best tensile properties. Vogt et al 16 also obtained vast improved results with considerably reduction in processing times to only 3 min as a function of temperature. When processing engineering thermoplastic polymers, it is necessary that the processing temperature is high enough to be able to melt the thermoplastic material and to enable a relatively quick heat transfer throughout the whole structure for homogeneous mixing.…”
Section: Introductionmentioning
confidence: 95%
“…14 The processing parameters for the manufacturing of thermoplastic composites are very important as these parameters such as processing temperature, pressure and time have a direct influence on the mechanical properties and performance of the final composite product depending on the individual machine and materials. 15,16 The development of composites of high temperature polymers with leather fibres via melt-mixing technique requires proper settings of processing parameters for ultimate performance of the composites. These parameters, especially temperature is critical in the processing of high temperature thermoplastic composites as low processing temperature will lead to nonhomogeneous distribution of fibres and on the other hand, higher processing temperature might result to thermal degradation of the fibres as well as the matrix.…”
Section: Introductionmentioning
confidence: 99%